2020
DOI: 10.1136/bmjdrc-2020-001227
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of 30-day unplanned hospital readmission among adult patients with diabetes mellitus: a systematic review with meta-analysis

Abstract: Adult patients with diabetes mellitus (DM) represent one-fifth of all 30-day unplanned hospital readmissions but some may be preventable through continuity of care with better DM self-management. We aim to synthesize evidence concerning the association between 30-day unplanned hospital readmission and patient-related factors, insurance status, treatment and comorbidities in adult patients with DM. We searched full-text English language articles in three electronic databases (MEDLINE, Embase and CINAHL) without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 72 publications
3
36
1
3
Order By: Relevance
“…The LOS among patients having a history of insulin administration on the admission time was increased by more than three times compared to those who had no history of insulin administration. This finding is in agreement with the report of previous studies [ 53 , 72 , 73 ]. This finding might be related to the side effects of insulin (i.e., hypoglycemia).…”
Section: Discussionsupporting
confidence: 94%
“…The LOS among patients having a history of insulin administration on the admission time was increased by more than three times compared to those who had no history of insulin administration. This finding is in agreement with the report of previous studies [ 53 , 72 , 73 ]. This finding might be related to the side effects of insulin (i.e., hypoglycemia).…”
Section: Discussionsupporting
confidence: 94%
“…Dozens of risk factors for readmission have been identified among patients with diabetes [ 19 22 •]. A recent systematic review and meta-analysis of 23 studies published through 2018 on more than 30 million patients provides the most complete data on a small set of commonly assessed risk factors [ 22 •].…”
Section: Epidemiology Of Readmissionsmentioning
confidence: 99%
“…Dozens of risk factors for readmission have been identified among patients with diabetes [ 19 22 •]. A recent systematic review and meta-analysis of 23 studies published through 2018 on more than 30 million patients provides the most complete data on a small set of commonly assessed risk factors [ 22 •]. The strongest risk factors identified were insurance type (Medicare/Medicaid vs. private), insulin use, hospital length of stay (LOS), and certain comorbidities (heart failure, respiratory disease, depression, and renal disease).…”
Section: Epidemiology Of Readmissionsmentioning
confidence: 99%
“…In our paper, male gender was a predictor of readmission within 90 days of discharge. Similarly, Soh et al showed that male gender is the predictor of 30-day unplanned hospital readmission among adult patients with diabetes mellitus [13]. However, in the papers of Chen et al [14] and Karunakaran et al [15], gender was not a significant predictor of 30-day hospital readmission in diabetes patients discharged from hospitals.…”
Section: Discussionmentioning
confidence: 98%
“…Retrospective analysis of a large US database, by Berry et al [12], found that when considering all conditions, the readmission rate increased in young adults peaked by middle age and decreased at age 65 years. In turn, in a recently published systemic review and meta-analysis, age ≥65 predicted unplanned hospital readmissions within 30 days of discharge among adult patients with diabetes mellitus [13].…”
Section: Discussionmentioning
confidence: 99%